Marriage Cancellation Caused by Falsification of Identity (Analysis of the Decision of the Syar'iyah Court of Banda Aceh City Number 99/Pdt.G/2019/MS.Bna): Pembatalan Perkawinan Disebabkan Pemalsuan Identitas (Analisis Putusan Mahkamah Syar’iya Kota Banda Aceh Nomor 99/Pdt.G/2019/MS.Bna) - Aziz, Nasaiy; Achyar, Gamal; Sari Dewi, Bela (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2021)
Based on the Compilation of Islamic Law in chapter 70, the decision of the marriage cord can also be made possible by marriage or by means of annulment of marriage, where the cancellation of marriage is caused by a violation or prohibition of marriage, while the prohibition to show damage, or something that is prohibited such as not meeting the requirements and pillars of marriage in domestic harmony. One of the cases of annulment of marriages at the syar'iyah court of Banda Aceh is the case with Number: 99/Pdt.G/2019/MS.Bna. In this case the husband as the applicant submits a request for annulment of marriage because the wife as the respondent is already married and heard the news from one of the respondent's family. Prior to marriage, the applicant knew that the respondent had never been married or was a virgin. However, in the judge's decision, the defendant's request was granted. In writing this thesis, the problem is how is the decision of the Syar'iyah Court of Banda Aceh City in case number 99/Pdt.G/2019/Ms.Bna regarding the application for annulment of marriage due to identity falsification and what is the basis for the judge's consideration in the decision. What is the view of Islamic law on the decision of the judges of the Banda Aceh City Sharia Court and the basis for legal considerations in case Number 99/Pdt.G/2019/Ms.Bna regarding the application for annulment of marriage due to identity falsification. The method used is using the library research method with the field method (rleid research). The results of the study show that in the decision number: 99/Pdt.G/2019/MS.Bna. The judge accepted the application for annulment of marriage submitted by the Petitioner's husband because the wife had falsified her identity or virgin status, but after it was known by the wife's family that she had been married for one year with her ex-husband and was a widow. Based on the analysis of Islamic law on the decision of the Banda Aceh City Sharia Court in deciding case Number 99/Pdt.G/2019/Ma.Bna. regarding the annulment of marriage due to identity falsification. the decision of the Panel of Judges in accepting the decision can cause a lot of damage in the future, such as adding to suffering for both parties.